2020
DOI: 10.1038/s41419-020-03242-x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine reverses chemoresistance via upregulation of p21WAF1/CIP1 and autophagy inhibition in ovarian cancer

Abstract: Overcoming drug-resistance is a big challenge to improve the survival of patients with epithelial ovarian cancer (EOC). In this study, we investigated the effect of chloroquine (CQ) and its combination with cisplatin (CDDP) in drug-resistant EOC cells. We used the three EOC cell lines CDDP-resistant A2780-CP20, RMG-1 cells, and CDDP-sensitive A2780 cells. The CQ-CDDP combination significantly decreased cell proliferation and increased apoptosis in all cell lines. The combination induced expression of γH2AX, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…However, drug-resistant cancer cells can survive the DNA damage induced by anticancer drugs through DNA repair pathways or bypassing cell cycle checkpoints ( 160 , 161 ); however, CQ can upregulate the expression of p21 WAF1/CIP1 to prevent this phenomenon and reverse the drug resistance of cancer cells. This function seems to depend on autophagy inhibition, but the connection is not yet clear ( 162 ). Many other functions of CQ depend on its inhibitory effect on autophagy.…”
Section: Progress On the Use Of Quinoline Antiparasitic Drugs For Treating Cancermentioning
confidence: 99%
“…However, drug-resistant cancer cells can survive the DNA damage induced by anticancer drugs through DNA repair pathways or bypassing cell cycle checkpoints ( 160 , 161 ); however, CQ can upregulate the expression of p21 WAF1/CIP1 to prevent this phenomenon and reverse the drug resistance of cancer cells. This function seems to depend on autophagy inhibition, but the connection is not yet clear ( 162 ). Many other functions of CQ depend on its inhibitory effect on autophagy.…”
Section: Progress On the Use Of Quinoline Antiparasitic Drugs For Treating Cancermentioning
confidence: 99%
“…The protein p21 CIP1 can be targeted by autophagy [ 97 , 98 , 99 ]. Under various conditions, inhibition of autophagy is able to stabilize p21 CIP1 levels [ 97 , 98 , 99 ].…”
Section: Autophagy Modulates Cell-cycle Regulatorsmentioning
confidence: 99%
“…The protein p21 CIP1 can be targeted by autophagy [ 97 , 98 , 99 ]. Under various conditions, inhibition of autophagy is able to stabilize p21 CIP1 levels [ 97 , 98 , 99 ]. Of note, a recent study demonstrates that the ectopic expression of one of the master transcription factors of lysosomal biogenesis, TFEB, also induces p21 CIP1 expression [ 100 ].…”
Section: Autophagy Modulates Cell-cycle Regulatorsmentioning
confidence: 99%
“…In vitro experiments have shown that chloroquine reverses cisplatin resistance in EOC cells, producing autophagy inhibition and lethal DNA damage by inducing p21WAF1/CIP1 expression [ 152 ]. Besides, autophagy inhibitors have been tested in combination with other anti-tumoral compounds.…”
Section: Drug Repurposing For Complementary Treatment For Ovarian Cancermentioning
confidence: 99%